Enhancing phototoxicity in human colorectal tumor cells through nanoarchitectonics for synergistic photothermal and photodynamic therapies - Almeida Junior, Alexandre Mendes; Ferreira, André Satoshi; Camacho, Sabrina Alessio; Moreira, Lucas Gontijo; Toledo, Karina Alves; Oliveira Junior, Osvaldo Novais; Aoki, Pedro Henrique Benites (ACSPublications, 2024)
Phototherapies are promising for noninvasive treatment of aggressive tumors, especially when combining heat induction and oxidative processes. Herein, we show enhanced phototoxicity of gold shell-isolated nanorods conjugated with toluidine blue-O (AuSHINRs@TBO) against human colorectal tumor cells (Caco-2) with synergic effects of photothermal (PTT) and photodynamic therapies (PDT). Mitochondrial metabolic activity tests (MTT) performed on Caco-2 cell cultures indicated a photothermal effect from AuSHINRs owing to enhanced light absorption from the localized surface plasmon resonance (LSPR). The phototoxicity against Caco-2 cells was further increased with AuSHINRs@TBO where oxidative processes, such as hydroperoxidation, were also present, leading to a cell viability reduction from 85.5 to 39.0%. The molecular-level mechanisms responsible for these effects were investigated on bioinspired tumor membranes using Langmuir monolayers of Caco-2 lipid extract. Polarization-modulation infrared reflection–absorption spectroscopy (PM-IRRAS) revealed that the AuSHINRs@TBO incorporation is due to attractive electrostatic interactions with negatively charged groups of the Caco-2 lipid extract, resulting in the expansion of surface pressure isotherms. Upon irradiation, Caco-2 lipid extract monolayers containing AuSHINRs@TBO (1:1 v/v) exhibited ca. 1.0% increase in surface area. This is attributed to the generation of reactive oxygen species (ROS) and their interaction with Caco-2 lipid extract monolayers, leading to hydroperoxide formation. The oxidative effects are facilitated by AuSHINRs@TBO penetration into the polar groups of the extract, allowing oxidative reactions with carbon chain unsaturations. These mechanisms are consistent with findings from confocal fluorescence microscopy, where the Caco-2 plasma membrane was the primary site of the cell death induction process.

As terapias fotônicas são promissoras para o tratamento não invasivo de tumores agressivos, especialmente quando combinam indução de calor e processos oxidativos. Neste estudo, demonstramos uma fototoxicidade aumentada de nanorods isolados de casca de ouro conjugados com azul de toluidina O (AuSHINRs@TBO) contra células tumorais colorretais humanas (Caco-2) por meio de efeitos sinérgicos das terapias fototérmica (PTT) e fotodinâmica (PDT). Testes de atividade metabólica mitocondrial (MTT) realizados em culturas de células Caco-2 indicaram um efeito fototérmico dos AuSHINRs devido à absorção de luz aprimorada pela ressonância plasmônica de superfície localizada (LSPR). A fototoxicidade contra células Caco-2 foi ainda maior com AuSHINRs@TBO, onde processos oxidativos, como a hidroperoxidação, também estavam presentes, resultando em uma redução da viabilidade celular de 85,5% para 39,0%. Os mecanismos moleculares responsáveis por esses efeitos foram investigados em membranas tumorais bioinspiradas utilizando monocamadas de Langmuir extraídas de lipídios de Caco-2. A espectroscopia de reflexão-absorção infravermelha com modulação de polarização (PM-IRRAS) revelou que a incorporação de AuSHINRs@TBO ocorre devido a interações eletrostáticas atrativas com grupos carregados negativamente do extrato lipídico de Caco-2, resultando na expansão das isotermas de pressão superficial. Sob irradiação, monocamadas de extrato lipídico de Caco-2 contendo AuSHINRs@TBO (1:1 v/v) exibiram um aumento de aproximadamente 1,0% na área de superfície. Esse efeito é atribuído à geração de espécies reativas de oxigênio (ROS) e sua interação com as monocamadas de extrato lipídico de Caco-2, levando à formação de hidroperóxidos. Os efeitos oxidativos são facilitados pela penetração dos AuSHINRs@TBO nos grupos polares do extrato, permitindo reações oxidativas com insaturações da cadeia carbônica. Esses mecanismos são consistentes com os achados de microscopia de fluorescência confocal, que mostraram que a membrana plasmática de Caco-2 foi o principal local do processo de indução da morte celular.
Aumentando a fototoxicidade em células tumorais colorretais humanas por meio de nanoarquitetônicas para terapias sinérgicas fototérmica e fotodinâmica
Keywords: Gold shell-isolated nanorods (AuSHINRs); Toluidine blue-O(TBO); Human colorectal tumorcells(Caco-2); Photodynamic therapy(PDT); Photothermal therapy(PTT)